Hagiology of Sufi Saints and the spread of Islam in South Asia - Muhammad Ismail (New Delhi: Jnanada Prakashan, 2018)
This book deals with the socio-religious and economic issues in South Asia. The work highlights the Hagiology of West Asian, North Indian and Bengali Sufi Saints and their role in the spread of Islam in South asia.
Includes Bibliographic references and index.
Keywords: Sufi Saints-- Islam-- South Asia